Nursing students' perception about humanized care: an integrative review - Bianca Marques dos Santos; Rose Mary Costa Rosa Andrade Silva; Eliane Ramos Pereira; Fabiana Lopes Joaquim; Ticiane Roberta Pinto Goés
ABSTRACT Objective: To analyze the productions of knowledge about the students' perception of humanized care. Method: Study of bibliographical revision of the integrative type. The databases Pubmed, Lilacs, Cuiden and the SciELO virtual library were chosen for selection in October 2017, using the health descriptors "Students, Nursing", "Perception" and "Humanization of assistance", in the languages Portuguese, English and Spanish. Results: Only eight studies were included that met the objectives of the study, where the majority portrays the Brazilian reality. Conclusion: Given the current discussion of society on the subject and the scarcity of publications, it is clear the need to adapt the academic field to complaints of society, as well as reflection of why the problem does not have a significant approach in international setting.